Basal cell carcinoma at the pinna - Sahoo, Soumick Ranjan; Nayak, Pallavi; Datta, Nilanjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Basal cell carcinoma (BCC) is the most common type of non melanoma cutaneous malignancy BCC usually present on sun exposed area such as nose, mandibular, periocular region. A review of the literature revealed only a few reports of BCC on the auricle or conchal bowl. Objectives were to report a case of BCC of right pinna. A 62 year old man presented to ENT OPD with a painless blackish lesion in the right pinna appreciated since 6 months and progressively increased to the present size. On local examination of the pinna a blackish plaque with irregular margins was appreciated in the cocha, helical crus and incisura. It was soft to firm in consistency and tenderness absent. Wide excision of the lesion with healthy margin done under local anesthesia. Histopathology of excised specimen confirmed the lesion as BCC. BCC of pinna is an uncommon external ear pathology which should be kept as a differential diagnosis of lesions of the pinna by the otorhinolaryngologist.